Assessment of Non-Fatal Occupational Injuries at a Tertiary Care Hospital - Sudhan , SM; Sowjanya, D; Nadaf , AA; Nayak, GH (Journal of Indian Academy of Forensic Medicine, 2024)
Occupational injuries are responsible for more lost time from work, productivity and working years of life than any other health conditions. The fatality due to occupational injuries are increasing but nonfatal injuries due to same cause are much more larger in number and most of them go without reporting. An effort has been made in this study to determine the pattern of nonfatal occupational related injuries. It is a cross sectional study. Data was collected from OPD and IPD patients of occupational related cases which had come to hospital. Qualitative color test for alcohol was performed. 50 cases of patients with non-fatal occupational injuries were studied. Majority of cases in agriculture occupation sector i.e., 29 cases (58%). 90% of cases were male and 10% of cases were female and age group between 18-27yrs (34%) followed by 30% of cases between 28-37 yrs and 24% between 38-47yrs. Majority of accidents occurred between 12pm-4pm and 4pm – 8pm i.e., 19 cases (38%) and 16 cases (32%) respectively. 60% of cases occurred in workers who had work experience of >5years, followed by 24% in 6 months 2 years of work experience. In majority of cases safety equipments were not available (72%) and 14% of cases had the habit of alcohol consumption and 8% of cases were tested positive for colour test of alcohol. Among cases, predominant type of injury was punctured wounds (36%), followed by laceration/avulsion (16%) and predominant body part affected were upper limbs (36% of cases) and lower limbs (30% of cases). Analysis of the data in our study revealed a number of factors that were strongly associated with occupational injury. Particular care should be exercised in educating the workers about workplace hazards, training and experience of workers employed in dangerous jobs, pre-recruitment medical check up and screening health examinations should be conducted regularly at work place.